JENIS LALAT BUAH Bactrocera spp PADA TANAMAN JAMBU KRISTAL Psidium guajava di Desa Bumiaji Kota Batu - I Made Indra Agastya; Hidayati Karamina (BUANA SAINS, 2016)
The purpose of this study is to identification the type of fruit flies and the sex ratio, which attack plants Psidium guajava, in the village of Bumiaji. This research was conducted by taking samples in the plantation exploration Psidium guajava, in the village of Batu Bumiaji and identification in the laboratory of Biology, University Tribhuwana Tunggadewi. The results show that the type of fruit flies consists of two species, Bactrocera carambolae with a sex ratio of 1: 3 and Bactrocera papayae with a sex ratio of 1: 2.